Multiphoton non-local quantum interference controlled by an undetected photon - Kaiyi Qian; Kai Wang; Leizhen Chen; Zhaohua Hou; Mario Krenn; Shining Zhu; Xiao-song Ma (Nature Communications, 2023)
Usually, observation of quantum interference in a non-local scenario (that is, when Alice’s measurement settings and Bob’s outcomes are space-like separated) relies on entanglement. Here, the authors experimentally show four-photon frustrated interference originating from the sources’ indistinguishability, without the need for entanglement.